Mapping urban heat island phenomenon: Remote sensing approach - Md. Hashim, N.; Asmala, A.; Abdullah, M. (Institution of Engineers, Malaysia., 2007)
This article investigates the application of remote sensing data for mapping urban heat island (UHI) phenomenon in an urbanised area of Selangor. The selected area covers Kajang, Cheras and Dengkil mukims in Selangor with total area of 4950 ha. The urban heat island was determined by using the land surface temperature (LST) information from thermal infrared band (Band 6) of Landsat image with 120 m pixel resolution. A subset of Landsat TM acquired on April 17, 1988 (path 127/row58) covers the urbanised mukims was used in this study. Erdas Imagine 8.5 was the main software for image classification of urban land covers in 1988, while GIS-Grid Calculator functions were used to derive land surface temperature. This study demonstrates the spatial variation of LST within urban blocks with temperature above 27.5o Celcius. About 3557 pixels (or approximately 32 ha of area) has been identified as UHI pixels in both Cheras and Kajang mukims. Urban impervious area near Pekan Bt 9, Cheras, Kajang town and Bandar Baru Bangi have been recognised areas with highest number of UHI-related pixels. The result revealed the effectiveness of remote sensing data application in analysing urban heat island-land surface temperature relationships in Selangor.